2009
DOI: 10.1177/097185240901300104
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Economic Activities with Special Reference to Women’s Participation and Empowerment in Rural Bangladesh

Abstract: Bangladesh is known as a predominantly male-dominated society with traditional and religious beliefs that restrict women's mobility and participation in economic and social activities. This article is based on national rural representative household-level data collected in 1987 and 2000 from 62 villages in Bangladesh jointly conducted by the International Rice Research Institute and Bangladesh Institute of Development Studies. First, this article depicts patterns of women's work and analyzes the factors that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 12 publications
(19 reference statements)
1
38
0
Order By: Relevance
“…Findings also indicated no participation of women in purchasing medicine/going to doctor for treatment of the ducks, while about 44% of haor women duck raisers were participated occasionally in feeding & collecting snails/ fish/earthworms and 14% of them participated frequently. The overall findings of participation of haor women in duck rearing activities were more focused on home-based activities which are also supported by others (Bose et al, 2009).…”
Section: Participation In Duck Rearing Activities (Dras)supporting
confidence: 82%
See 2 more Smart Citations
“…Findings also indicated no participation of women in purchasing medicine/going to doctor for treatment of the ducks, while about 44% of haor women duck raisers were participated occasionally in feeding & collecting snails/ fish/earthworms and 14% of them participated frequently. The overall findings of participation of haor women in duck rearing activities were more focused on home-based activities which are also supported by others (Bose et al, 2009).…”
Section: Participation In Duck Rearing Activities (Dras)supporting
confidence: 82%
“…The WEIs as presented in Table 3 clearly indicated that women were empowered slightly above the average level in overall decision making activities. Bose et al (2009) showed that the value of the empowerment index for women is generally low, indicating that women are seldom given the opportunities to express their ideas for execution. In the study, the findings showed that the average WEI was 1.08 that means haor women are empowered through economic contributions to their family income.…”
Section: Women Empowerment In Intra-family Decision Making Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the methodology used by Bose et al (2009), "Women decision making Index" (DMI) has been constructed in this article in consideration of women participation in household decision making process in carrying out PH activities. We assigned the lowest value (=0) when the decision is taken by male alone, in this case women being lowest "empowered".…”
Section: Decision Making Indexmentioning
confidence: 99%
“…A number of studies have been conducted on women's activities during 80s [9], [10], [11], [12], [13], [14], [15]. These studies found that contribution of women to socio-economic development were not visible, perhaps due to a set of social norms that enabled men to dominate women [16]. In recent years, however, a large number of young girls are working in readymade garment [17].…”
Section: Introductionmentioning
confidence: 99%